2019
DOI: 10.1111/jpi.12623
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates SGLT2 inhibitor‐induced diabetic ketoacidosis by inhibiting lipolysis and hepatic ketogenesis in type 2 diabetic mice

Abstract: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are effective hypoglycemic agents that can induce glycosuria. However, there are increasing concerns that they might induce diabetic ketoacidosis. This study investigated the effect of melatonin on SGTL2i-induced ketoacidosis in insulin-deficient type 2 diabetic (T2D) mice. The SGLT2i dapagliflozin reduced blood glucose level and plasma insulin concentrations in T2D mice, but induced increases in the concentrations of plasma β-hydroxybutyrate, acetoacetate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…In particular, visceral adipocyte hypertrophy results in decreased insulin sensitivity, a weakened insulin anti-lipolytic effect, and enhanced lipolytic activity in adipocytes (Roden and Shulman, 2019). Studies have found that the anti-lipolytic effect of insulin can be adjusted through the AKT/PKA/HSL signaling pathway (Yin et al, 2019), and inhibiting excessive lipolysis of adipose tissue (Park et al, 2020) is an important way to treat metabolic diseases. Consistent with previous results, we found that adipocytes expanded, IRS1 phosphorylation increased, AKT activity decreased, and insulin signal transduction was impaired, while PKA-mediated HSL activity was upregulated and the ability to release FFA into the circulation was enhanced in the WAT of ZDF rats.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, visceral adipocyte hypertrophy results in decreased insulin sensitivity, a weakened insulin anti-lipolytic effect, and enhanced lipolytic activity in adipocytes (Roden and Shulman, 2019). Studies have found that the anti-lipolytic effect of insulin can be adjusted through the AKT/PKA/HSL signaling pathway (Yin et al, 2019), and inhibiting excessive lipolysis of adipose tissue (Park et al, 2020) is an important way to treat metabolic diseases. Consistent with previous results, we found that adipocytes expanded, IRS1 phosphorylation increased, AKT activity decreased, and insulin signal transduction was impaired, while PKA-mediated HSL activity was upregulated and the ability to release FFA into the circulation was enhanced in the WAT of ZDF rats.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin (MT) is a tryptophan‐derived substituted indoleamine that is synthesized by the pineal gland and peripheral organs 6,7 . Previous studies have found that MT has been widely used to treat various diseases due to its antioxidant, anti‐inflammation, antidiabetes, and antiobesity properties 8–10 . Indeed, MT has been demonstrated to alleviate many liver diseases, such as heavy metal‐induced liver injury, liver inflammation, and liver fibrosis 11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…These effects seem to be independent of the improvement of the glycolipid metabolism or tissue inflammation but are related to the alleviation of local oxidative stress in adipose tissue [ 33 ]. Several studies reported the risk of SGLT2 inhibitors on liver steatosis by promoting fat lysis and its hepatic transporting [ 25 , 34 ]. However, increasing evidences supported that SGLT2 inhibitors could improve hepatic steatosis in rodents or humans [ 32 , 33 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%